Dynamic Optical Coherence Tomography of Cutaneous Blood Vessels in Melasma and Vessel Response to Oral Tranexamic Acid. Issue 6 (8th November 2020) - Pomerantz, Hyemin; Christman, Mitalee P.; Bloom, Bradley S.; Lederhandler, Margo; Feng, Hao; Holmes, Jon; Geronemus, Roy G.
Abstract : Background and Objectives: Melasma may be related to aberrant blood vessels, but there has been no report on the utility of dynamic optical coherence tomography (D‐OCT) in studying vessel characteristics in melasma. We studied the characteristics of cutaneous blood vessels in melasma and the effects of oral tranexamic acid (TXA) with D‐OCT. Study Design/Materials and Methods: Six patients with moderate to severe melasma had a D‐OCT scanning of the areas on the face affected by melasma and not affected by it. Three of them had scans within 3 months after starting oral TXA and at a follow‐up visit. Blood flow at different depths of the skin and vessel diameter were compared between the melasma and normal skin. For those taking oral TXA, we compared the percent change of blood flow and diameter between the melasma and normal skin. Results: Dermal blood flow and vessel diameter were greater in the melasma skin than in the normal skin. Oral TXA reduced dermal blood flow in both the melasma and normal skin, but the reduction was more dramatic in the lesional melasma skin. Conclusions: D‐OCT findings that (i) dermal blood vessels in melasma are increased in size and flow and (ii) oral TXA reduced the vessel size and flow, providing evidence supporting the relationship between melasma and cutaneous blood vessels. D‐OCT may be utilized in measuring response to treatments targeting melasma. Lasers Surg. Med. © 2020 Wiley Periodicals LLC